Genome-wide association and functional annotation analyses reveal candidate genes and pathways associated with various ewe longevity indicators in U.S. Katahdin sheep - Pinto, Luis F. B.; Lewis, Ronald M.; Rocha, Artur O.; Freking, Brad A.; Murphy, Tom W.; Wilson, Carrie S.; Nilson, Sara M.; Burke, Joan M.; Brito, Luiz F. (Frontiers in Genetics, 2025)
Ewe longevity indicators are complex traits that are lowly heritable, expressed late in life, and sex-limited, making them challenging to include in breeding programs. In this context, genome-wide association studies (GWASs) can provide more information on the complex genetic control of these traits. Therefore, the primary objective of this study was to carry out association analyses for 8 longevity-related traits in 12,734 Katahdin ewes. A total of 126 associations at the chromosome-wide level and 3 at genome-wide level were found. These associations involved 86 single-nucleotide polymorphisms (SNPs) located across 22 chromosomes, with 24 of these SNPs associated with two or more traits. The variants overlapped with genes previously associated with prolificacy (APOH, NLRP9, H3PXD2A, CKB, and HERC4), ovarian follicle pool (GALNT13, TMEM150B, and BRSK1), synthesis and release of reproductive hormones (SULT1B1, LEF1, and EIF5), and early pregnancy events (ITGAV, HADH, ZNFX1, ZSCAN4, EPN1, FBXW8, NOS1, ST3GAL4, and GFRA1). Moreover, genes related to response to stress or pathological conditions (ADCY5, HADH, ATRNL1, LEP, IL11, NLRP9, PRKCG, PRKCA, NEDD4L, FECH, CTNNA3, HECTD1, LRRTM3, and zinc-finger proteins), growth performance (GRID2, MED13L, DCPS, and LEP), and carcass traits (CMYA5 and SETD3) were also implicated. Metabolic pathways such as oxytocin signaling and cardiac-related pathways were enriched. These findings suggest that longevity indicators in Katahdin ewes are highly polygenic traits influenced by a combination of voluntary and involuntary culling reasons. Candidate genes and metabolic pathways influencing reproductive performance and health may play a key role in the functional longevity of Katahdin ewes.